Increasing returns to smart cities. Issue 2 (2nd May 2013) - Lööf, Hans; Nabavi, Pardis; Kourtit, Karima; Nijkamp, Peter; Partridge, Mark D.
Abstract Increased urbanization, global warming and sustainable growth belong to the major contemporary policy challenges. Today cities are home to more than 50 per cent of the world population, the largest 600 urban centres generate about 60 per cent of global GDP, and the agglomerated areas are responsible for 75 per cent of world carbon emissions. The UN estimates that 70 per cent of the world's growing population will live in cities by 2050. At the same time the world population is expected to increase from 7 billion people to 9 billion. Thus, the total number of people living in cities will be almost doubled within a period of less than 4 decades. This paper discusses two hypotheses on how this will affect climate change and economic growth.